1971
DOI: 10.1039/tf9716701143
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of rehydration of crystalline anhydrides. Manganous formate

Abstract: The anhydride resulting from the dehydration of manganous formate dihydrate is crystalline and its skeletal structure is distinct from the dihydrate. Under the proper conditions of temperature and water vapour pressure the freshly dehydrated anhydride rehydrates readily and completely to the dihydrate. Rehydration against time curves have been obtained for anhydrides prepared from the dihydrate which was in the form of individual single crystals, crystalline powder, ground powder and reactor-irradiated powder.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Even though metal formate dihydrates are model compounds for hydration/dehydration experiments and their decomposition properties have been well documented, [14] their dehydration products have only been characterized by Xray powder diffraction (Mg, [15] Mn, [16] Fe, [17] Zn [18] ), and their structures are not known. The dehydration of nickel and cobalt formate dihydrate only results in amorphous products.…”
Section: Introductionmentioning
confidence: 99%
“…Even though metal formate dihydrates are model compounds for hydration/dehydration experiments and their decomposition properties have been well documented, [14] their dehydration products have only been characterized by Xray powder diffraction (Mg, [15] Mn, [16] Fe, [17] Zn [18] ), and their structures are not known. The dehydration of nickel and cobalt formate dihydrate only results in amorphous products.…”
Section: Introductionmentioning
confidence: 99%
“…The rehydration of manganous formate produced from the vacuum dehydration of the dihydrate has been studied in detail by Eckhardt et al (1971). This material was found to rehydrate smoothly and completely to the dihydrate composition, unlike nickel and manganous oxalates, which rehydrate only very slowly after an initial, rapid reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The behavior is quite similar to that of K Z C O~.~/~H~O in that the rate is very strongly inhibited by small pressures of water vapor. The reported activation energy tu = 1.20 X 10-19J; vapor pressure data (Eckhardt et al, 1971) were employed to compare the predictions of this model to the reported rate data using the following convenient form of Eq. 16:…”
Section: Dehydratlon Ratesmentioning
confidence: 99%